A Feasibility Study on the Implementation of a Solar Powered Water Desalination Plant - John Adebisi; Eliaser Indongo; Muyiwa Amusan (Journal of Digital Food, Energy & Water Systems)
Water desalination plants powered by solar energy represent a viable solution for addressing a part of the water needs in areas without a reliable water supply. In this case extending the electric grid and water delivery to remote communities remain challenging for some countries. Using Namibia as a case study, this work carried out a feasibility study on the extent of which, solar energy could be used to power the entire desalination process thereby aiding groundwater usable for human consumption. This process includes but not limited to desalination of underground wells and boreholes as solution to the water shortage problem in remote places. In this study, a solar-powered desalination technique that could enhance the process of clean water provision to villagers is proposed. It further compares and analyzed various desalination technologies to determine the best fit based on the dryness of areas. Ohawuwanga Village in Namibia was used for evaluation purpose with a sampling instrument-questionnaire which determine the village's daily water consumption and corresponding power required. Modelling, simulation and analysis of the system was carried out using MATLAB Simulink in terms of energy consumption. Other parameters considered in this research are cost, water recovery ratio, salt removal factor, durability and market analysis. The research revealed that electrodialysis is the best technology for desalination in terms of efficient power consumption amidst other factors compared.